2018
DOI: 10.1111/pim.12576
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase controls experimental Strongyloides infection

Abstract: Infection with Strongyloides sp. induces a host immune response, predominantly the Th2 type, that is able to eliminate the parasite. However, little is known about the role of the nitric oxide (NO) mediator, induced by the enzyme nitric oxide synthase (NOS), in strongyloidiasis. Therefore, in this study, we investigated the immune response of mice genetically deficient in the enzyme inducible nitric oxide synthase (iNOS ), infected with Strongyloides venezuelensis. C57BL/6 wild-type (WT) and iNOS mice were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, neither pharmaceutical inhibition of nitric oxide synthesis nor iNOS knockout in mice abrogated resistance to circulating L. sigmodontis [55]. More recently, iNOS −/− mice infected with Strongyloides venezuelensis showed increased susceptibility to infection [56]. These results illustrate that mechanisms of protection or susceptibility defined in one model system cannot be simply assigned to all helminth-host interactions: rather particular differences can be critical in favoring initial inflammatory responses that have a major role in inducing protection during helminth infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither pharmaceutical inhibition of nitric oxide synthesis nor iNOS knockout in mice abrogated resistance to circulating L. sigmodontis [55]. More recently, iNOS −/− mice infected with Strongyloides venezuelensis showed increased susceptibility to infection [56]. These results illustrate that mechanisms of protection or susceptibility defined in one model system cannot be simply assigned to all helminth-host interactions: rather particular differences can be critical in favoring initial inflammatory responses that have a major role in inducing protection during helminth infections.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from schistosomes, the important role of NO was suggested also in the control of other helminths such as Trichinella spiralis [21][22][23], Brugia malayi [24,25], Strongyloides venezuelensis [26,27] and Taenia crassiceps [28]. However, particular effector mechanisms of NO/ RNS antiparasitic actions remain rather unexplored.…”
mentioning
confidence: 99%
“…ROS are released from both the host immune effector cells and through degradation of haemoglobin. Induced nitric oxide synthase provides protection against Strongyloides venezuelensis infection in mice, as inducible nitric oxide synthase (iNOS) knock out (KO) resulted in mice being more susceptible to infection (Rodrigues et al ., 2018 ). Previous studies have found that NO can contribute to either parasite clearance or to susceptibility by exacerbating inflammation that worsens disease manifestation, or facilitates parasite killing (Diliani and Dondji, 2017 ).…”
Section: Discussionmentioning
confidence: 99%